Lift Me Up by Looking Down: Social Comparison Effects of Narratives - Krause, Stefan; Weber, Silvana (Frontiers in Psychology, 2018)
Stories are a powerful means to change recipients’ views on themselves by being transported into the story world and by identifying with story characters. Previous studies showed that recipients temporarily change in line with a story and its characters (assimilation). Conversely, assimilation might be less likely when recipients are less identified with story protagonists or less transported into a story by comparing themselves with a story character. This may lead to changes, which are opposite to a story and its characters (contrast). In two experiments, we manipulated transportation and experience taking via two written reviews (Experiment 1; N = 164) and by varying the perspective of the story’s narrator (Experiment 2; N = 79) of a short story about a negligent student. Recipients’ self-ratings in comparison to others, motives, and problem-solving behavior served as dependent variables. However, neither the review nor the perspective manipulation affected transportation or experience taking while reading the story. Against our expectations, highly transported recipients (in Study 1) and recipients with high experience taking (in Study 2) showed more persistency working on an anagram-solving task, even when controlling for trait conscientiousness. Our findings are critically discussed in light of previous research.